On spherical indicatrices of curves in Galilean 4-space Gâ‚„ - Unluturk, Yasin; YÄ±lmaz, SÃ¼ha (IndoMS, 2019)
In this study, we indroduce spherical indicatrices of curves in four dimensional Galilean space. Moreover, we characterize these curves in terms of Frenet-Serret vector fields in four dimensional Galilean space. Frenet-Serret apparatus of these curves are obtained in terms of base curve's Frenet invariants. Additionally, some theorems are given regarding characterizations of spherical indicatrices of curves in four dimensional Galilean space.